The Unpublished correspondence of Mme de Genlis and Margaret Chinnery - Yim, D (Voltaire Foundation, 2017)
This fascinating correspondence between Mme de Genlis and her English admirer Margaret Chinnery was discovered at a private art gallery in London in 1996. Margaret Chinnery was an intelligent, wealthy mother of three who educated her own children, and the letters offer proof that she implemented Mme de Genlis’s method, as expounded in the latter’s novel Adèle et Théodore. The correspondence documents a warm friendship which began in 1802, and which came to crisis point, as did so many of Mme de Genlis’s friendships, with the publication of her Mémoires in 1825. Approximately half the letters to Margaret Chinnery date from 1802, when the Chinnery family and the de facto family member, the violinist G. B. Viotti, came to Paris during the Peace of Amiens. Most of the others date from 1807, when Mme de Genlis sent her adopted son Casimir Baecker to London in an attempt to repeat the successes of his Paris harp concerts. The forty letters from Mme de Genlis are extraordinarily candid in their description of her daily activities, her financial situation, and her hopes and disappointments. They reveal an emotionally fragile, driven woman, almost pitiable in her obsession to promote her favourite pupil Casimir. The letters provide valuable information on Mme de Genlis’s educational works, her novels and on her periodical contributions that were in progress at the time of writing, as well as on many of her other manuscripts. Some of the letters describe her attempts, through the Chinnery family and Viotti, to sell her manuscripts in England. Because copies of Margaret Chinnery’s letters have been preserved the subjects treated in the letters are not only contextualised, but are given continuity and coherence. In addition, over twenty-two related letters and documents provide an elucidating backdrop to the main body of the correspondence. This is the only known correspondence that documents a friendship between Mme de Genlis and an English woman and the completeness of its preservation makes it a valuable resource indeed. List of illustrations Abbreviations Preface Acknowledgements Editor’s introduction i. The manuscripts ii. Editorial principles iii. Editorial symbols Biographical notes on the Chinnery family General introduction i. The 1802-1803 letters ii. The 1807-1808 letters The unpublished correspondence of Mme de Genlis and Margaret Chinnery and related documents in the Chinnery family papers Appendix Works cited Index